1995
DOI: 10.1007/bf01676709
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive receptors expressed by tumor cells and platelets: novel targets for therapeutic anti-metastatic strategies

Abstract: In vitro and in vivo studies have demonstrated that adhesive interactions between tumor cells and platelets may play a central role in the metastatic process. Ultrastructural studies have demonstrated that platelets appear to enhance the development of arrested tumor emboli into a secondary metastatic colony. Platelet adhesive glycoprotein receptors and their immunorelated counterparts expressed by tumor cells participate in tumor-induced platelet aggregation, which may be an early step in the development of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Plateletpoor plasma obtained with argatroban was collected from 14 patients before surgery (before) and on postoperative day 1 (POD 1), and plasma concentrations of VEGF, sP-selectin, and vWf were determined as described in "Subjects and methods" including intravasation into the bloodstream, adhesion to vascular endothelial cells of distant organs, tumor cell proliferation, and invasion into the target organ. Recent evidence suggests that platelet-tumor and tumor-endothelial interactions participate in the primary adhesive events required for the initiation of the metastatic process [12,19]. vWf and its adhesive ligand, glycoprotein (GP) Ibα on platelets, have been shown to play an important role in the formation of metastasis via tumor-platelet aggregation and thrombus formation [12,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plateletpoor plasma obtained with argatroban was collected from 14 patients before surgery (before) and on postoperative day 1 (POD 1), and plasma concentrations of VEGF, sP-selectin, and vWf were determined as described in "Subjects and methods" including intravasation into the bloodstream, adhesion to vascular endothelial cells of distant organs, tumor cell proliferation, and invasion into the target organ. Recent evidence suggests that platelet-tumor and tumor-endothelial interactions participate in the primary adhesive events required for the initiation of the metastatic process [12,19]. vWf and its adhesive ligand, glycoprotein (GP) Ibα on platelets, have been shown to play an important role in the formation of metastasis via tumor-platelet aggregation and thrombus formation [12,20].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that platelet-tumor and tumor-endothelial interactions participate in the primary adhesive events required for the initiation of the metastatic process [12,19]. vWf and its adhesive ligand, glycoprotein (GP) Ibα on platelets, have been shown to play an important role in the formation of metastasis via tumor-platelet aggregation and thrombus formation [12,20]. P-selectin, an adhesion molecule that mediates interactions of platelets, has also been shown to have a crucial role in developing metastasis [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated platelets also induce the formation of a fibrin clot by carrying coagulation factors and providing a catalytic surface for the major interactions of the coagulation cascade. Because there exists a clear link between atherosclerotic vascular disease, inflammation, tumor metastasis, and thrombosis (1)(2)(3), it is important to identify the mechanisms of platelet aggregation that have pathobiologic, prognostic, and treatment-related relevance. Studies on cancer metastasis have shown that some human and animal tumor cells possess platelet aggregation-inducing abilities that correlate with their metastatic potential (2,3).…”
mentioning
confidence: 99%
“…Because there exists a clear link between atherosclerotic vascular disease, inflammation, tumor metastasis, and thrombosis (1)(2)(3), it is important to identify the mechanisms of platelet aggregation that have pathobiologic, prognostic, and treatment-related relevance. Studies on cancer metastasis have shown that some human and animal tumor cells possess platelet aggregation-inducing abilities that correlate with their metastatic potential (2,3). Interactions between tumor cells and platelets have been considered to facilitate the arrest of tumor cell cluster in the microcirculation with the subsequent formation of experimental metastasis.…”
mentioning
confidence: 99%